-(-3v+u)+3(-3u+v)=

Simple and best practice solution for -(-3v+u)+3(-3u+v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-3v+u)+3(-3u+v)= equation:


Simplifying
-1(-3v + u) + 3(-3u + v) = 0

Reorder the terms:
-1(u + -3v) + 3(-3u + v) = 0
(u * -1 + -3v * -1) + 3(-3u + v) = 0
(-1u + 3v) + 3(-3u + v) = 0
-1u + 3v + (-3u * 3 + v * 3) = 0
-1u + 3v + (-9u + 3v) = 0

Reorder the terms:
-1u + -9u + 3v + 3v = 0

Combine like terms: -1u + -9u = -10u
-10u + 3v + 3v = 0

Combine like terms: 3v + 3v = 6v
-10u + 6v = 0

Solving
-10u + 6v = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-10u + 6v + -6v = 0 + -6v

Combine like terms: 6v + -6v = 0
-10u + 0 = 0 + -6v
-10u = 0 + -6v
Remove the zero:
-10u = -6v

Divide each side by '-10'.
u = 0.6v

Simplifying
u = 0.6v

See similar equations:

| 2x-18=-40 | | 7.4-9.2=2.6+5.3 | | 8n+2n-6+9=5 | | -10r+12r=-18 | | ax+bx-4=-9 | | 3(x+2)=2x+5 | | 48p+(-32)=16 | | x+15-4x-45= | | 5-a/2=7 | | 6n-54=-12n+36 | | 8x+5=t | | 3(9+5)=3*9+3*5 | | 4u+-7u=9 | | 12x+2=122 | | 35x^2-161x-70=0 | | 5-7n+4n=18-64 | | Y=-0.01X^2+0.6X+5.8 | | 16x^2-24x+6=0 | | 4n+20=53-2a | | h(t)=-16t^2+40t+9 | | 2(f+-7)=-10 | | -14=-18+n | | -10k=0 | | 59-13x=-139-7x | | -6x-5=4x+25 | | 87+(-96)= | | -4(x+2)=6x+10+12 | | -6x-5=4x+5 | | -3=3+v | | 13=6+(-r) | | 5+3*b=8-5*b | | 2x^2+19x+30=0 |

Equations solver categories